2018
DOI: 10.2217/cer-2017-0079
|View full text |Cite
|
Sign up to set email alerts
|

Authors’ lack of awareness and use of core outcome set on postoperative pain in children is hindering comparative effectiveness research

Abstract: Further discussions about the adequacy of COS for acute pediatric pain, as well as interventions to increase the uptake of COS may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…(iii) We did not observe any relationship between the number of outcomes recommended by a COS and its rate of uptake. However, in a survey about the uptake of the Ped-IMMPACT COS for pediatric acute and chronic pain, some authors of systematic reviews felt that the six domains in the COS were too many [40]. It is possible, however, that it is the perceived burden on patients to complete the measures that lead to reluctance to implement them, as noted by Mulla et al in their study of the uptake of the IMMPACT COS for chronic pain [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(iii) We did not observe any relationship between the number of outcomes recommended by a COS and its rate of uptake. However, in a survey about the uptake of the Ped-IMMPACT COS for pediatric acute and chronic pain, some authors of systematic reviews felt that the six domains in the COS were too many [40]. It is possible, however, that it is the perceived burden on patients to complete the measures that lead to reluctance to implement them, as noted by Mulla et al in their study of the uptake of the IMMPACT COS for chronic pain [21].…”
Section: Discussionmentioning
confidence: 99%
“…Only one of these studies, which assessed a COS for ankylosing spondylitis, noted some increase in uptake of the full COS after publication (0% RCTs before versus 20% RCTs after). The survey investigating the uptake of the PedIMMPACT COS found a lack of awareness of the COS, with only a third of authors of trials and systematic reviews who completed the survey being aware of the COS [40]. Lack of awareness was cited as an issue by a report of a similar survey for the IM-MPACT COS for chronic pain [41].…”
Section: Discussionmentioning
confidence: 99%
“…We recently conducted a survey among the authors of the RCTs and systematic reviews published in the field of postoperative paediatric pain to analyse their awareness about the PedIMMPACT core outcome set and whether they find these recommendations appropriate (Boric et al., ). The responses of the surveyed authors indicated that some authors were indeed not aware of the PedIMMPACT core outcome set, while others stressed that the core outcome sets were too complicated, that they encompass too many domains, and that they are difficult to implement in practice.…”
Section: Discussionmentioning
confidence: 99%
“…The responses of the surveyed authors indicated that some authors were indeed not aware of the PedIMMPACT core outcome set, while others stressed that the core outcome sets were too complicated, that they encompass too many domains, and that they are difficult to implement in practice. When asked which outcome domains they would personally include in a core outcome set for acute paediatric pain, more than half of the surveyed authors indicated that they would use the following in order of frequency: pain intensity, additional analgesia, additional opioid analgesia, pain‐free, symptoms and adverse events, physical recovery, emotional response and sleep (Boric et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…2532 Barriers to implementation by trialists may include lack of awareness about core outcomes among trialists, resource constraints, lack of incentives, and complexities in measuring patient-reported outcomes. 33,34 Without consistent reporting of these core outcomes, there is little scope for end-users such as guideline producers and policymakers to capitalize on their potential benefits. However, little remains known about the perspectives of stakeholders on the use of core outcomes, and frameworks and interventions for the implementation of core outcomes are lacking.…”
mentioning
confidence: 99%